Exploring novel optical soliton solutions for the stochastic chiral nonlinear Schrodinger equation: Stability analysis and impact of parameters - Islam, S. M. Rayhanul; Arafat, S. M. Yiasir; İnç, Mustafa (World Scientific Publ Co Pte Ltd, 2025)
The primary aim of this investigation is to uncover novel optical soliton solutions (OSSs) and conduct a comprehensive stability analysis of a particular model. The extraction of OSSs is facilitated through two potent techniques: the advanced auxiliary equation and the (w/g)-expansion approaches, both proven to be highly effective in revealing soliton solutions in various nonlinear evolution equations. In this paper, we provide an in-depth exposition of the obtained solutions, elucidating them both graphically and in their physical context. Furthermore, we investigate the influence of diverse parameters on these results by presenting several graphical representations. Additionally, we delve into the stability of equilibria and conduct a thorough phase-plane analysis of the model. To provide a broader context, we also offer a comparative discussion of our solutions in relation to previous works in the field. Considering the significance of the stochastic chiral nonlinear Schrodinger equation in soliton theory, the solutions obtained here hold the potential to illustrate intricate physical phenomena and find applications across diverse fields in the realm of communication systems.
Keywords: Stochastic chiral nonlinear Schrodinger equation; advanced auxiliary equation method; (w/g)-expansion approach; stability analysis; optical soliton solutions